2020
DOI: 10.1055/a-1141-5989
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation in Primary Aldosteronism

Abstract: Primary aldosteronism (PA) is the most common cause of secondary hypertension. Increasing evidence has demonstrated an increased cardiovascular risk in patients with PA compared to those with essential hypertension (EH), including atrial fibrillation (AF), the most prevalent arrhythmia among adults that is associated with an elevated risk of subsequent cerebro-cardiovascular adverse events. The mechanisms of inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 93 publications
(119 reference statements)
0
22
0
1
Order By: Relevance
“…Atrial fibrillation is associated with increased risks of stroke, heart failure and mortality (28). Excessive aldosterone is a major contributing factor to atrial fibrillation genesis (9,12), as shown in the German Conn's Registry which reported a prevalence rate of atrial fibrillation of 7.1% among 553 PA patients (29). Seccia et al also demonstrated that the PA was highly prevalent in hypertensive patients with unexplained atrial fibrillation in prospective appraisal on the prevalence of primary aldosteronism in hypertensive (PAPPHY) study (30).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Atrial fibrillation is associated with increased risks of stroke, heart failure and mortality (28). Excessive aldosterone is a major contributing factor to atrial fibrillation genesis (9,12), as shown in the German Conn's Registry which reported a prevalence rate of atrial fibrillation of 7.1% among 553 PA patients (29). Seccia et al also demonstrated that the PA was highly prevalent in hypertensive patients with unexplained atrial fibrillation in prospective appraisal on the prevalence of primary aldosteronism in hypertensive (PAPPHY) study (30).…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical studies have shown that aldosterone induces left ventricular hypertrophy and fibrosis which is associated with left ventricular diastolic dysfunction (8,(36)(37)(38)(39)(40). The left ventricular diastolic dysfunction has a prominent influence on atrial structure and function which also contributed to the atrial fibrillation genesis (8,12,41).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations